Archaeometric case studies on decorations of pre‐Columbian pottery using X‐ray spectroscopy maps and profiles: Archäometrische Fallstudien an vorkolumbischer Keramik mittels Röntgenspektroskopie‐Karten und ‐Profilen. Issue 6 (June 2017) - Dietrich, D.; Mehner, T.; Del‐Solar‐Velarde, N.; Nickel, D.; Lampke, T.; Chapoulie, R.; Butters, L.J. Castillo
Abstract: The potential of chemical information obtained by scanning electron microscopy (SEM) based methods is examined for archaeometric studies on polychrome decorations of ceramics. Achieved on polished block sections, the feasibility and benefits are demonstrated as case studies using pre‐Columbian pottery (Wari, Moche, and Cajamarca). Elemental mapping and profiling by X‐ray spectroscopy (EDS) allow separate consideration of the paste in the body, slip, binder and pigments in the polychrome decoration. Compositional profiles across decorative layers substantiate the use of manganese ores for the formation of jacobsite as black pigment. To enlighten trade relations, technological transfer and shared heritage of pre‐Columbian cultures in Peru, the results provide information about local or non‐local pottery production.